2022
DOI: 10.1002/jeab.731
|View full text |Cite
|
Sign up to set email alerts
|

Applications of operant demand to treatment selection I: Characterizing demand for evidence‐based practices

Abstract: Various treatment approaches have been determined efficacious for improving child behavior outcomes. Despite a variety of evidence‐based options, consumers often disregard empirically supported treatments to pursue alternatives that lack empirical support, such as ‘fad' therapies. The choice to pursue therapies lacking empirical support has been considered a ‘gamble’ on therapeutic outcomes and this form of risky choice has historically been explained using various cognitive heuristics and biases. This report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 58 publications
4
24
0
Order By: Relevance
“…That is, one would assume that a perfectly rational agent would favor choices more associated with larger and more probable returns (i.e., EBPs) over alternatives with lesser, or at least less probable, returns (i.e., fads, pseudoscience). Indeed, Rational Choice Theory holds that individuals seek to maximize utility (Hantula, 2017), and in the case of behavioral therapies, should choose EBPs more often than not (Gilroy et al, 2022). However, research with human and nonhuman animals has found that organisms rarely behave rationally and regularly demonstrate patterns of "irrational" or "suboptimal" choice (Ainslie, 1975(Ainslie, , 1992.…”
Section: Behavioral Economics and Treatment-related Choicementioning
confidence: 99%
See 4 more Smart Citations
“…That is, one would assume that a perfectly rational agent would favor choices more associated with larger and more probable returns (i.e., EBPs) over alternatives with lesser, or at least less probable, returns (i.e., fads, pseudoscience). Indeed, Rational Choice Theory holds that individuals seek to maximize utility (Hantula, 2017), and in the case of behavioral therapies, should choose EBPs more often than not (Gilroy et al, 2022). However, research with human and nonhuman animals has found that organisms rarely behave rationally and regularly demonstrate patterns of "irrational" or "suboptimal" choice (Ainslie, 1975(Ainslie, , 1992.…”
Section: Behavioral Economics and Treatment-related Choicementioning
confidence: 99%
“…That is, findings from behavioral science have been used to characterize the situations in which organisms deviate from optimal (e.g., EBPs) to suboptimal choices (e.g., fad therapies; Mazur, 1987;Odum, 2011). Abstracting this perspective to treatment choice, a behavioral economic approach may help characterize the situations in which caregivers deviate from optimal prospects (EBPs) and fall prey to questionable (potentially unsafe) treatment practices Gilroy et al, 2022). For example, behavioral economic research has found treatment-related choices to be more reliably influenced by proximal environmental factors, such as delays (Call et al, 2015;.…”
Section: Behavioral Economics and Treatment-related Choicementioning
confidence: 99%
See 3 more Smart Citations